2017
DOI: 10.1097/md.0000000000007262
|View full text |Cite
|
Sign up to set email alerts
|

The effect of platelet-rich plasma on reducing blood loss after total knee arthroplasty

Abstract: Background:Efficacy and safety of platelet-rich plasma (PRP) compared with control for preventing postoperative bleeding after total knee arthroplasty (TKA) is controversial. We performed a meta-analysis of randomized controlled trials (RCTs) to determine whether PRP might reduce blood loss and improve function following TKA.Methods:PubMed, Medline, Embase, Web of Science, and the Cochrane Library were searched to identify RCTs comparing PRP with control for patients undergoing unilateral TKA. The mean differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…However, there is low to very low quality evidence regarding the effectiveness of most of these topical agents, except for cadexomer iodine . Autologous platelet‐rich plasma (PRP) has been used for 30 years in a variety of surgical situations, including blood loss reduction and promotion of tissue regeneration . Although individual small‐scale studies reported an effective use of PRP in VLU management, strong evidence for its effectiveness from high‐quality randomized controlled trials (RCTs) is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is low to very low quality evidence regarding the effectiveness of most of these topical agents, except for cadexomer iodine . Autologous platelet‐rich plasma (PRP) has been used for 30 years in a variety of surgical situations, including blood loss reduction and promotion of tissue regeneration . Although individual small‐scale studies reported an effective use of PRP in VLU management, strong evidence for its effectiveness from high‐quality randomized controlled trials (RCTs) is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In the first stage of screening titles and abstracts, 79 references were selected. Full texts were scrutinised against the inclusion and exclusion criteria, with a final inclusion of 29 SRs (Figure ) . Reasons for exclusion of studies at the second stage are presented by topic and clinical indication in Files …”
Section: Resultsmentioning
confidence: 99%
“…One SR focusing on clinical efficacy of the intraoperative use of PRP during total knee arthroplasty was identified . This SR was deemed of moderate methodological quality (AMSTAR score 10/16).…”
Section: Resultsmentioning
confidence: 99%
“…37 Despite mixed evidence, several studies have indicated that PRP reduces pain and blood loss and improves shortterm outcomes of arthroplasty. [38][39][40][41] Although the use of PRP injections during TSA has not been well studied, the relative safety and the evidence of PRP's positive effect on soft-tissue healing make the use of PRP a prudent decision to optimize TSA outcomes.…”
Section: Discussionmentioning
confidence: 99%